THE INFLUENTIAL FACTORS OF PURSUING AN ACCOUNTING MAJOR: AN EXAMINATION OF HIGH SCHOOL STUDENTS IN MALAYSIA - Charis Yee Hui-En; Lee Teck-Heang; Har Wai-Mun; Cheng Boon-Liat (International Journal of Accounting, Finance and Business, 2023)
Pursuing a degree at a university can be one of the major decisions to be made for high school students. The paper aims to examine the influential factors that influence high school students’ intentions to major in accounting. This study adopted Theory of Planned Behavior as the theoretical foundation and explores whether personal factors, reference factors, and academic performance affect students' intentions to major in accounting. A total of 156 high school students responded to this questionnaire survey. Results showed that personal factors, such as students' positive perspective in accounting, genuine interest in accounting-related subjects, and career prospects in the future, were found to be key determinants of accounting majors. In addition, academic performance was found to be an important determinant of accounting majors and therefore students with better high school grades are likely to choose accounting as a major. This study contributes to the understanding of the factors that influence the intentions of high school students to choose accounting as a degree-seeking major in college or university.